Tigecycline exerts an antitumoral effect in oral squamous cell carcinoma. (6th April 2015) - Ren, A; Qiu, Y; Cui, H; Fu, G
<x xml:space="preserve">Abstract</x> Objective To explore whether antibacterial drug tigecycline could exert an antitumoral effect in oral squamous cell carcinoma (OSCC). Materials and Methods Two OSCC cell lines Tca8113 and KB were used in this study. To investigate the cytostatic effects of tigecycline in OSCC, cell growth was tested by trypan blue staining, MTT assay, and Brdu immunofluorescence staining. Then, the apoptosis proportion was measured by FITC Annexin‐V and PI labeling, and cell cycle was determined by PI staining. The expression of caspase 3 (CASP3) and cell cycle regulatory protein was detected by Western blot assay. Finally, the clonogenesis and tumorigenesis capacity were analyzed by soft agar growth and xenograft model. Results Here, we showed that tigecycline significantly inhibited cell growth and proliferation in OSCC cell lines Tca8113 and KB. It did not induce cell apoptosis but led to an increase of cells in G0/G1 phase with down‐regulation of cyclin E2 (CCNE2) and cyclin‐dependent kinase4 (CDK4) protein expression. We also showed that tigecycline inhibited colony formation in soft agar and reduced tumor growth in a xenograft model. Conclusion Our results suggested that tigecycline might be used as a novel candidate agent for the treatment of OSCC.